Clinical-epidemiological characteristics and etiological structure of benign mechanical jaundice syndrome: an 11-year single-center study - Maksymenko, M. V.; Susak, Y. M.; Dorosh, V. M.; Lobanova, O. M.; Havryliuk, R. O. (General Surgery, 2025)
Benign mechanical jaundice (BMJ) is a common condition in gastroenterological and surgical practice. Despite its clinical significance, most studies involve mixed etiologies (benign and malignant), complicating the assessment of the features specific to benign forms. Data on the seasonality, trends in hospitalization frequency, and clinical‑demographic characteristics of patients with BMJ remain limited. Objective – to analyze the etiological structure, demographic profile, clinical presentation, hospitalization trends, and seasonality of benign mechanical jaundice based on 11 years of single‑center data. Materials and methods. A retrospective‑prospective single‑center study was conducted involving 1,187 patients diagnosed with BMJ and hospitalized at Kyiv City Clinical Hospital of Emergency Care between 2013 and 2024. The diagnosis was based on clinical, laboratory, and imaging findings, with malignant pathology excluded. Descriptive, correlation, regression, and variance statistics were applied. Results. The most common cause of BMJ was choledocholithiasis (73.6%), followed by indurative pancreatitis (7.7%), major duodenal papilla stenosis (7.1%), and Mirizzi syndrome (2.9%). Females predominated (57.8%), and the mean age was 64.7±14.3 years. Seasonal variation was statistically significant (p<0.001), with peaks in January, May, and November. A moderate positive correlation was observed between total bilirubin levels and time to hospitalization (r=0.482; p<0.001). A gradual increase in BMJ cases from 2014 to 2021 was noted (R2=0.47). Conclusions. Choledocholithiasis is the leading cause of benign mechanical jaundice. Patients typically present late, with higher bilirubin levels correlating with delayed hospitalization. A clear pattern of seasonality was identified, which may inform improved healthcare resource planning. This study is the first in Ukraine to provide a comprehensive analysis of benign mechanical jaundice in a large cohort with the exclusion of malignant cases.